Research trends and hotspots in the surgical treatment of peripheral nerve injuries of the upper limb from 2000 to 2024: a bibliometric visualization study - Ruan, Jian; He, Hekun; Li, Xueyuan; Chen, Hong (Frontiers in Neurology, 2025)
PurposeSurgical treatment plays a crucial role in the management of peripheral nerve injuries of the upper limb, but little bibliometric analysis has been conducted on it. This study was aimed to examine the global trends and hotspots in the field of Peripheral nerve injuries of the upper limb.MethodsPublications on the surgical treatment of peripheral nerve injuries of the upper limb in the Web of Science database were collected between 2000 to 2024. CiteSpace and VOSviewer software was applied to visualize and analyze publications, countries, institutions, journals, authors, references, and keywords.ResultsA total of 751 articles were collected, the most active countries in this field were the United States and China. The authors with the most publications were Mackinnon, Susan E from the United States, and Xu WD and Gu YD from China. JOURNAL OF HAND SURGERY AMERICAN VOLUME was the journal with the most published. Based on keywords, the current research hotspots primarily revolved around nerve transfer, brachial plexus and reconstruction.ConclusionThe results of this bibliometric study provide clinical trends and hotspots in the surgical treatment of peripheral nerve injuries of the upper limb over the past 24 years, which may help researchers to identify clinical trends and explore new treatment in the field of peripheral nerve injuries.